2003
DOI: 10.1007/s00439-003-1004-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA sequence polymorphisms of five ethnic populations from northern China

Abstract: To study the mitochondrial DNA (mtDNA) polymorphisms in a total of 232 individuals from five ethnic populations (Daur, n=45; Ewenki, n=47; Korean, n=48; Mongolian, n=48; Oroqen, n=44) in northern China, we analyzed the control region sequences and typed for a number of characteristic mutations in coding regions (especially the region 14576-16047), by direct sequencing or restriction-fragment-length-polymorphism (RFLP) analysis. With the exception of 14 individuals belonging to the European-specific haplogroups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
3
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(147 citation statements)
references
References 30 publications
12
130
3
2
Order By: Relevance
“…The haplogroup status was further confirmed by detecting additional variations in other regions as described in our previous studies (Yao et al 2002aKong et al 2003a). A segment covering region 10171-10659 of the rCRS, which was suggested to be informative in defining East Asian specific haplogroups (Yao et al 2002a), was adopted to specify the phylogenetic status of the F* or R9* mtDNAs (the asterisk attached to haplogroups indicates that the sample was not able to be further classified into the sub-clade(s) of the haplogroup) in our previous studies (Yao et al 2000(Yao et al , 2002a(Yao et al ,c, 2003Yao and Zhang 2002;Kong et al 2003a) and unpublished data. For those published data sets (not from our laboratory) with only HVS-I and/or HVS-II information available, we recognized the potential F2 types by matching and/or near-matching with the identified F2 types that have been tested for coding region information.…”
Section: Data Analysessupporting
confidence: 61%
See 2 more Smart Citations
“…The haplogroup status was further confirmed by detecting additional variations in other regions as described in our previous studies (Yao et al 2002aKong et al 2003a). A segment covering region 10171-10659 of the rCRS, which was suggested to be informative in defining East Asian specific haplogroups (Yao et al 2002a), was adopted to specify the phylogenetic status of the F* or R9* mtDNAs (the asterisk attached to haplogroups indicates that the sample was not able to be further classified into the sub-clade(s) of the haplogroup) in our previous studies (Yao et al 2000(Yao et al , 2002a(Yao et al ,c, 2003Yao and Zhang 2002;Kong et al 2003a) and unpublished data. For those published data sets (not from our laboratory) with only HVS-I and/or HVS-II information available, we recognized the potential F2 types by matching and/or near-matching with the identified F2 types that have been tested for coding region information.…”
Section: Data Analysessupporting
confidence: 61%
“…All of the individuals were confirmed to be unrelated before sampling and were given informed consent. To better understand the phylogeny of haplogroup F2, the previously reported data sets (Yao et al 2000(Yao et al , 2002a(Yao et al ,c, 2003Tsai et al 2001;Kivisild et al 2002;Oota et al 2002;Yao and Zhang 2002;Kong et al 2003a;Tajima et al 2003) were also included. As a result, a total of 3,090 mtDNAs from 57 populations across China were examined, and their detailed information was illustrated in Table 1.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In haplogroup C, the Han Chinese originating from the farming people 1,9,10 are concentrated in one group. Meanwhile, PW4 is clustered into another group with minorities in northern China, northern Asians and ancient nomads, 2,7,[12][13][14][15][16][17][18][19] suggesting that PW4 is closely related to the nomads. In haplogroups D4 and M10, the ancient people from Pengyang consistently occupy the same nodes as northern Asians, northern minorities of China and ancient nomads, showing a close genetic relationship among them.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to conflicts between these two ethnic groups in the frontier, the nomads assimilated gradually into the Han Chinese population or became the minorities in northern China. 1,2 Therefore, the minorities in northern China and other northern Asians can trace their origins to the ancient nomads. 1 Archeological studies of the Zhongzhuang and Wangdahu sites, located in Pengyang in the southern Ningxia area in China (Figure 1), indicated that they were occupied from B770 BC to 256 BC during the Dongzhou period.…”
Section: Introductionmentioning
confidence: 99%